A Mouse Called MIIKA - Haig, Matt, 1975-; Mould, Chris (New York : Alfred A. Knopf, 2021)
"A independent mouse sets out on a quest to prove that cheese exists, and learns to appreciate other creatures along the way"--
Keywords: Mice -- Juvenile fiction; Cheese -- Juvenile fiction; Animals -- Juvenile fiction